Climate policy and power producers: The distribution of pain and gain. (March 2020) - Doda, Baran; Fankhauser, Sam
Abstract: Climate policies do not affect all power producers equally. In this paper, we evaluate the supply-side distributional consequences of emissions reduction policies using a simple and novel partial equilibrium model where production takes place in technology-specific sites. In a quantitative application hydro, wind and solar firms generate power combining capital and sites which differ in productivity. In contrast, the productivity levels of coal, gas and nuclear technologies are constant across sites. We parameterise the model to analyse the effects of stylised tax and subsidy schemes. Carbon pricing outperforms all other instruments and, crucially, leads to more equitable outcomes on the supply side. Technology-specific and uniform subsidies to carbon-free producers result in a greater welfare cost and their supply-side distributional impacts depend on how they are financed. Power consumption taxes have exceptionally high welfare costs and should not be the instrument of choice to reduce emissions or to finance subsidies aiming to reduce emissions. Highlights: We study the distributional impacts of climate policies on power generators. Carbon pricing is cost-effective and leads to a more equitable supply-side outcome. A technology-specific (TS) subsidy is inferior to a technology-neutral (TN) one. A TN subsidy also implies a more uniform distribution of the net policy burden. Using revenues from a power consumption tax is a poor way to finance subsidies.